2009
DOI: 10.1007/s10750-009-9707-y
|View full text |Cite
|
Sign up to set email alerts
|

Feeding at different plankton densities alters invasive bighead carp (Hypophthalmichthys nobilis) growth and zooplankton species composition

Abstract: Invasive Asian carps Hypophthalmichthys spp. are an ecological threat to non-native aquatic ecosystems throughout the world, and are poised to enter the Laurentian Great Lakes. Little is known about how these filter-feeding planktivores grow and impact zooplankton communities in mesotrophic to oligotrophic systems like the Great Lakes. Our purpose was to determine how different plankton densities affect bighead carp H. nobilis biomass and how bighead carp affect zooplankton species composition. We conducted a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 26 publications
2
33
1
Order By: Relevance
“…However, recent studies have demonstrated that bighead and silver carps can adversely affect the water quality and native fish populations. For example, Borics et al, (2000), Cooke et al (2009) and Lin et al (2014) reported that bigheaded carps contributed significantly to the development of high algal biomass and reduced water clarity, while Sampson et al (2009) found considerable diet overlap among native fishes and bigheaded carps, which may cause decreased fitness in native fish populations. In addition, the combined stocking of these species caused a decline in the abundance of cladocerans and copepods in eutrophic lakes in China where bigheaded carps were introduced (Yang et al, 1999;Shao et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent studies have demonstrated that bighead and silver carps can adversely affect the water quality and native fish populations. For example, Borics et al, (2000), Cooke et al (2009) and Lin et al (2014) reported that bigheaded carps contributed significantly to the development of high algal biomass and reduced water clarity, while Sampson et al (2009) found considerable diet overlap among native fishes and bigheaded carps, which may cause decreased fitness in native fish populations. In addition, the combined stocking of these species caused a decline in the abundance of cladocerans and copepods in eutrophic lakes in China where bigheaded carps were introduced (Yang et al, 1999;Shao et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the combined stocking of these species caused a decline in the abundance of cladocerans and copepods in eutrophic lakes in China where bigheaded carps were introduced (Yang et al, 1999;Shao et al, 2001). Thus, these fishes constitute a considerable ecological threat to aquatic ecosystems where they are not native (Chick and Pegg, 2001;Xie and Chen, 2001;Cooke et al, 2009). Accordingly, bigheaded carp introduction and stocking to natural waters have been stopped and banned in the last decades in several countries, including Hungary (Boros et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Dong and Deshang (1994) mentioned that for plankton organisms about 70 μm dia., the removal rates by bighead carp were similar to those by silver carp. Cooke et al (2009) studied the effect of the amount of plankton on the development of bighead carp and they found out that there was a close interrelation between the biomass of the phytoplankton and the fish growth. The authors underlined that the insufficient amount of plankton biomass could be a limiting factor for growth.…”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with the observations of Trushenski and Kohler (2007), in which preslaughter stress was observed to increase fillet aldehyde concentrations after short-term frozen storage in Hybrid Striped Bass (Morone chrysops♀ x M. saxatilis♂). 8 www. siftdesk.…”
Section: Discussionmentioning
confidence: 99%